â€œTransaksi Ekonomi Modernâ€ Multi Level Marketing dalam Perspektif Hukum Islam - M Zikwan (UNIVERSITAS BONDOWOSO, 2023)
The development of the times and information technology has an impact on the activities of human life. Mualia of social politics and economics. Various models and types of transactions also accompany the times, including multi-level marketing. Multi-level marketing is a type of transaction where consumers can act as marketing by becoming a member of a company that implements a multi-level marketing sales system. Members will benefit from sales and bonuses obtained for being a member. In practice, multi-level marketing often gives the impression of a transaction that can harm other parties and is even considered a transaction full of deception. Therefore this article attempts to provide an overview of multi-level marketing transactions that are permissible in Islam. In this article the researcher uses a library approach, the main source in this research is written sources in the form of books, manuscripts, documents and others. In essence, a multi-level marketing transaction is an innovation and development of the type of buying and selling transaction, therefore a multi-level marketing transaction is a legal, syar'i transaction as long as it has the principle of not containing elements of usury, not gharar, fair transparency and so on.